ANALISI FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM PADA MASA PANDEMI COVID-19 (STUDI KASUS PADA UMKM KLUBAN DI BANJARATMA) - Warpuah; Dwi Harini; Slamet Bambang Riono (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2022)
The impact of the Covid-19 pandemic has affected many various fields, including the people's economy. The affected economic sectors include Micro, Small and Medium Enterprises (MSMEs), both culinary and handicraft businesses and. Their income is declining. This is due to the decline in people's purchasing power. Various efforts were made to deal with the possible business risks faced. However, MSME actors are still faced with various problems, both technical and nontechnical. This condition is a challenge in order to prepare for capital expenditures and the flow of the impact of the pandemic. Various strategies are carried out in order to keep the business running. If the Covid-19 pandemic continues, it is not impossible that some business actors will be able to go out of business to close their businesses. This prediction certainly threatens the Indonesian national economy. This study aims to find out what factors affect the income of MSMEs during the Covid-19 pandemic. The population in this study was 30 members of the Club MSME actors in Banjaratma Village. This research. The results of the factor analysis stated that in this study, 10 factors were found that influenced the decline in MSME income during the Covid-19 pandemic in Banjartma Village. These factors are: social distancing factors, PSBB factors, raw material factors, sales factors, technology factors, fund assistance factors, influencer factors, banking factors, consumption factors, and structural policy factors